Deteksi Level Pengetahuan Terkait Covid 19 di Kalangan Mahasiswa Perguruan Tinggi Negeri, Kawasan Perbatasan NKRI-RDTL - Yunawati Sele; Fincensius Oetpah; Vinsensia Ulia Rita Sila (Postgraduate, University of Mataram, 2022)
This research was conducted with the aim of revealing the level of knowledge related to COVID-19 among state university students, in the NKRI-RDTL border area. This study includes a qualitative descriptive study involving the population, namely all active students of state universities, Timor University, which are located in the border area of ​​the Republic of Indonesia-RDTL. By using a simple random sampling technique, obtained 1181 students as respondents. The research instrument in the form of a knowledge questionnaire related to covid was distributed to respondents offline and also online using the google form. The results showed that 17.7% of respondents had knowledge at a low level, 62.66% of respondents had knowledge at a moderate level, while 19.64% of respondents had knowledge at a high level. Among the 4 aspects of knowledge, knowledge on the etiology and symptom aspects, as well as aspects of preventing the spread of covid-19, are at a high level with an average value of each aspect, namely 85.61 and 83.09. Meanwhile, knowledge on aspects of risk groups and aspects of the spread of COVID-19 is at a low level with an average value of 51.54 and 54.19. This needs attention because the quality of knowledge basically has a relationship with attitudes and behavior related to COVID-19